KONFLIK SOSIAL DAN POLITIK DALAM KUMPULAN CERPEN DRAMA ITU BERKISAH TERLALU JAUH KARYA PUTHUT EA: KAJIAN SOSIOLOGI SASTRA - Fithroh Wahidah (Buana Bastra, 2018)
This study aimed to describe the social and political conflicts contained in the collection of short stories Drama Tells Too far work of Puthut EA and to describe thecorrelation between the short story collection The play was a story Too far work of PuthutEA with reality night history of Indonesian society. Sources of data in this study is the textcontained in the collection of short stories Drama Tells Too far work of Puthut EA. Whilethe research data is an excerpt sentence, description, dialogue, and other important mattersin the collection of short stories Drama Tells Too far work of Puthut EA. Data obtained byreading and writing techniques. Data were analyzed with the approach of sociology ofliterature and descriptive analysis techniques. The validity of the data obtained byconducting triangulation is triangualasi methods, sources of data and theory. These resultsindicate the existence of social and political conflict are contained in the collection of shortstories Drama Tells Too Far work of Puthut EA, containing social conflicts, among others:(1) gender conflict, namely: the oppression of women, (2) racial conflict, namely:discrimination of race Chinese, (3) inter-religious conflicts, namely: distrust ofcommunism, (4) conflict of interest, namely: the imposition of a leader, (5) interpersonal conflicts, namely: distrust of others, (6) the conflict between social classes, namely: socialinequality. Containing the political conflict, among others: (1) the weapons of battle and (2)the strategy politik. Correlation between the short story collection That play was a storyToo Far of Puthut EA works with historical reality of Indonesian society, among others: (1)The 1998 riots (2) The increase in fuel (3) Ethnic Discrimination (4) Dispute people of thesame religion (5) arrest Without Accompanied Official Letter (6) Violations of humanrights and (7) Poverty.